2008
DOI: 10.1073/pnas.0712386105
|View full text |Cite
|
Sign up to set email alerts
|

Profound functional and signaling changes in viable inflammatory neutrophils homing to cystic fibrosis airways

Abstract: Blood neutrophils recruited to cystic fibrosis (CF) airways are believed to be rapidly killed by resident bacteria and to passively release elastase and other toxic by-products that promote disease progression. By single-cell analysis, we demonstrate that profound functional and signaling changes readily occur within viable neutrophils recruited to CF airways, compared with their blood counterparts. Airway neutrophils have undergone conventional activation, as shown by decreased intracellular glutathione, incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
169
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 127 publications
(185 citation statements)
references
References 45 publications
12
169
1
2
Order By: Relevance
“…In particular, CF airway neutrophils undergo active exocytosis of primary granules, leading to massive release of enzymes (e.g., elastase, myeloperoxidase) that damage the airway tissue and perpetuate inflammation. More intriguingly, we also observed that CF airway neutrophils express high levels of markers conventionally found on long-lived APCs, including class II MHC, the costimulatory molecule CD80, and the chemoattractant receptor of Th2 cells (CD294), all of which suggest profound reprogramming (4).…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…In particular, CF airway neutrophils undergo active exocytosis of primary granules, leading to massive release of enzymes (e.g., elastase, myeloperoxidase) that damage the airway tissue and perpetuate inflammation. More intriguingly, we also observed that CF airway neutrophils express high levels of markers conventionally found on long-lived APCs, including class II MHC, the costimulatory molecule CD80, and the chemoattractant receptor of Th2 cells (CD294), all of which suggest profound reprogramming (4).…”
mentioning
confidence: 73%
“…Blood was treated with ammonium chloride to lyse RBCs, after which blood leukocytes were spun down and washed with PBS-EDTA. Leukocytes from blood and airway were prestained at 4˚C with Live/Dead (Life Sciences) and anti-CD16 and -CD63 (both from BioLegend) to enable gating of live neutrophils (4). After a wash with PBS-EDTA, leukocytes were equilibrated in serum-free RPMI 1640 (Cellgro) at 4˚C for $45 min.…”
Section: Glucose-uptake Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a growing body of data has emerged supporting the belief that inflammatory dyregulation in CF may occur early in life preceding infection and may be prompted by noninfectious stimuli (37). In addition, a fundamental intrinsic abnormality of inflammatory cells, including epithelial cells (1), neutrophils (38), lymphocytes, and granulocytes (39), has been proposed as a leading cause of inflammation. Our results confirm previous observations that CF cells express IL-18 at both the gene and protein level (5).…”
Section: Discussionmentioning
confidence: 99%
“…In the blood of CF patients, the level of apoptosis of neutrophils appears similar to the level of neutrophil apoptosis of healthy subjects, but the interaction of CF airway neutrophils with CF airway epithelial cells reduces their level of apoptosis compared with non-CF neutrophil-airway epithelial cell interaction [50]. Interestingly, Tirouvanziam and colleagues recently established that CF airways contain a significant fraction of nonapoptotic viable neutrophils [51]. They demonstrated that profound functional and signaling changes readily occur within viable neutrophils when recruited to CF airways.…”
Section: Editorialmentioning
confidence: 99%